Prospects for the Development of Eurasian Integration in the Field of Expanding Export Cargo Flows of Russian Gas to Friendly Countries amid the Escalation of the Energy Crisis in the World - T. Yu. Safonova (Евразийская интеграция: экономика, право, политика, 2023)
Aim. In 2022, the shortage of energy carriers on the world market was directly affected by sanctions against the Russian energy sector and terrorist attacks on the Nord Stream and Nord Stream —2 gas pipelines, while scientific publications do not present global calculations of the volumes of Russian gas falling out of world circulation. The aim is to assess the volumes of Russian gas falling out of global turnover.Tasks. Identification of prospects for the development of Eurasian integration in the field of expanding export cargo flows of Russian gas to friendly countries against the background of the escalation of the energy crisis in the world taking into account exogenous and endogenous factors influencing changes in the production and consumption of Russian gas.Methods. Methods of system and comparative analysis, scientific generalization, expert assessments, forecasting methods.Results. The author presents an analysis of Russia’s role in global gas s upplies, an assessment of falling export volumes, as well as a short-term forecast of changes in pipeline gas cargo flows according to optimistic, basic and pessimistic scenarios.Conclusion. According to the author, in order to exclude significant losses in gas production in Russia and to implement an optimistic scenario, it is important to accelerate the timing of the unification of the western and eastern gas transmission systems, as well as the implementation of investment projects for the construction of gas pipeline capacities “Power of Siberia — 2”, “Soyuz — Vostok”, “Turkish Stream — 2”.